2014
DOI: 10.1016/j.neuroimage.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Decreased norepinephrine transporter availability in obesity: Positron Emission Tomography imaging with (S,S)-[11C]O-methylreboxetine

Abstract: Objectives Noradrenergic dysfunction is implicated in obesity. The norepinephrine transporter (NET) regulates the synaptic availability of norepinephrine. However, NET availability has not been previously characterized in vivo in obese people using Positron Emission Tomography (PET) imaging. Here we report findings evaluating NET availability in individuals with obesity and matched lean (i.e., normal weight) comparison subjects. Methods Seventeen obese but otherwise healthy individuals with a mean±SD body ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 36 publications
4
60
1
Order By: Relevance
“…Distribution volume ratios (DVRs) were calculated using the occipital lobe as the reference region. The occipital lobe has been found to have one of the lowest concentrations of NET [19, 29] and has thus been used as a reference region in earlier works [11, 15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution volume ratios (DVRs) were calculated using the occipital lobe as the reference region. The occipital lobe has been found to have one of the lowest concentrations of NET [19, 29] and has thus been used as a reference region in earlier works [11, 15]. …”
Section: Methodsmentioning
confidence: 99%
“…A promising radioligand is 11 C labeled (S,S) 2-[(2-methoxyphenoxy)phenylmethyl]morpholine (MeNER), also called methylreboxetine (MRB), having an in vitro IC 50 of 2.5 nM [14]. It has been used to investigate NET density in normal controls, cocaine addicts [11] and obese population [15]. A fluorine analog of MRB, the [ 18 F]FMeNER-D2 has been used to study NET binding density in patients with major depressive disorders [16] and ADHD [17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these obese mice were shown to have higher levels of resting corticosterone and an elevated stress-induced corticosterone response in comparison to their normal weight counterparts. Increased glucocorticoids may result in depression through neuronal death, decreased neurogenesis, hippocampal atrophy, alterations in neurotropic proteins, and decreased synaptic excitability [8] which may be regulated by increased systemic inflammation [7,23,25] or insulin resistance [26].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive reviews on the potential mechanisms driving the bidirectional association between obesity and depression can be found elsewhere [3][4][5] and undoubtedly involve a number of psychological (e.g., self-esteem) [5], behavioral (e.g., repeated dieting) [5], and physiological (e.g., glucocorticoids) [6] mechanisms. While depression resulting from obesity may be caused by dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis and neurological alterations (e.g., decreased synaptic excitability) [7][8][9], depression may also result in overweight/obesity through an increased desire to consume calorie-rich foods [10,11]. Physical activity may play a critical role in mitigating this bidirectional association as it has been shown to reduce the risk of overweight/obesity [12] and depression [13,14], plausibly due to its reduction on HPA axis activity [15], as well as, of course, other factors such as increased energy expenditure [16] and improved self-esteem [5].…”
Section: Introductionmentioning
confidence: 99%
“…[17]). A recent study showed that the binding potentials of norepinephrine transports are decreased in the thalamus in obese as compared to non-obese individuals [35]. PET imaging has also shown that energy balance and weight loss is related to CNS receptor occupancy of the cannabinoid receptors, which are known to regulate mood and memory in addition to appetite [36].…”
Section: Techniques To Study the Cns In Clinical Researchmentioning
confidence: 99%